2016
DOI: 10.1186/s40035-016-0065-1
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of autophagy and mitochondrial function in Parkinson’s disease

Abstract: Parkinson’s disease (PD) is the second most common neurodegenerative disease. Increasing evidence supports that dysregulation of autophagy and mitochondrial function are closely related with PD pathogenesis. In this review, we briefly summarized autophagy pathway, which consists of macroautophagy, microautophagy and chaperone-mediated autophagy (CMA). Then, we discussed the involvement of mitochondrial dysfunction in PD pathogenesis. We specifically reviewed the recent developments in the relationship among se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
61
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(64 citation statements)
references
References 105 publications
(112 reference statements)
3
61
0
Order By: Relevance
“…In this study, we found that celastrol (1) increases protein levels of PINK1 and DJ-1 but represses LRRK2 expression, (2) enhances MAPK/ERK activation, and (3) celastrol maintains mitochondrial membrane potential and ATP production under MPP + treatment. Increasing evidence suggests that PINK1 and DJ-1 are essential for mitochondrial quality control [40]. DJ-1 overexpression induces ERK-dependent mitophagy and protects against rotenone-induced apoptosis [33].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that celastrol (1) increases protein levels of PINK1 and DJ-1 but represses LRRK2 expression, (2) enhances MAPK/ERK activation, and (3) celastrol maintains mitochondrial membrane potential and ATP production under MPP + treatment. Increasing evidence suggests that PINK1 and DJ-1 are essential for mitochondrial quality control [40]. DJ-1 overexpression induces ERK-dependent mitophagy and protects against rotenone-induced apoptosis [33].…”
Section: Discussionmentioning
confidence: 99%
“…Major features of mitochondrial dysfunction in PD include ROS overproduction, ATP depletion, mitochondrial DNA depletion, and caspase release. Mitochondrial toxins rotenone and MPTP can impair the mitochondrial function through inhibiting the activity of complex I, whereas suppression of complex I could result in abnormal OPA1 oxidation, which would subsequently lead to abnormality in mitochondrial structure and neurodegeneration of dopaminergic neurons …”
Section: Mitophagy and Neurodegenerative Diseasesmentioning
confidence: 99%
“…Importantly, mutation in PD‐associated genes such as Pink1 has also been shown to contribute to dysregulation of a number of these cellular processes including mitochondrial dysfunction (Wang et al . ).…”
mentioning
confidence: 97%
“…Oxidative stress has been shown to affect key processes such as nucleic acid stability, ion channels functionality, and structure and function of cellular proteins ultimately culminating in neuronal death (Uttara et al 2009;Zhao et al 2017). Importantly, mutation in PD-associated genes such as Pink1 has also been shown to contribute to dysregulation of a number of these cellular processes including mitochondrial dysfunction (Wang et al 2016).…”
mentioning
confidence: 99%